Total synthesis of notoryne - Senapati, Sibadatta; Das, Shyamsundar; Ramana, Chepuri V. (Journal of Organic Chemistry, 2018)
The structure of notoryne comprises a halogenated 2,2'-bifuranyl moiety along with a terminal cis-enyne unit. In this work, we document the first total synthesis of notoryne, confirming its assigned relative and absolute configurations. The devised route comprises a glucose diacetonide-derived chiral pool intermediate as the starting point and 5-endo bromo-etherification for making the key bis-furan unit, anomeric C-allylation, as well as a relay cross-metathesis to install the cis-enyne unit.

Total synthesis of (+)-petromyroxol, (-)-iso-petromyroxol, and possible diastereomers - Mullapudi, Venkannababu; Ahmad, Iram; Senapati, Sibadatta; Ramana, V, Chepuri (ACS Omega, 2020)
The total synthesis of (+)-petromyroxol (1) and its seven diastereomers including the ()-tso-petromyroxol (2) is described. The employed strategy involves the use of easily available CS-epimeric epoxides 5 and 5' and nonselective anomeric C1-allylation, proceeding with or without inversion at C2 thereby giving the possibility of synthesizing all possible diastereomers. Extensive two-dimensional (2D) NMR analyses of all eight diastereomers have been carried out to assign the chemical shifts of the central carbons land the corresponding attached hydrogens and to learn how the C/H-chemical shifts of the tetrahydrofuran ring were influenced by the adjacent centers.

Concise/catalytic approach for the construction of the C14-C28 fragment of eribulin - Senapati, Sibadatta; Ramana, V, Chepuri (Organic & Biomolecular Chemistry, 2021)
A simple approach for the synthesis of the C14-C28 fragment of eribulin has been developed by employing a one-pot gold-catalyzed alkynol cyclization/Kishi reduction to construct the 1,5-cis-tetrahydropyran unit and a cross-metathesis/Sharpless asymmetric dihydroxylation-cycloetherification to install the 1,4-trans-tetrahydrofuran ring. Use of easily accessible building blocks, ease of operation and catalytic transformations as key reactions for the construction of THF/THP units highlight the current approach.

Synthesis of four diastereomers of notoryne and their C-13 NMR chemical shifts analysis - Senapati, Sibadatta; Das, Shyamsundar; Dixit, Ruchi; Vanka, Kumar; Ramana, V, Chepuri (Journal of Chemical Sciences, 2021)
In this manuscript we document the details of the synthesis of four diastereomers of notoryne. The synthesis of one of the diastereomer having a similar relative stereochemistry of substituents on the both THF rings like notoryne, however, being the relative stereochemistry between the bridging carbon of these two THF units is changed from anti to syn has been executed mainly to learn how the ring carbon chemical shifts vary with this change. Interestingly, the deviations are found mainly for the carbons of THF ring that bears the Br-group. In addition to this isomer, three more diastereomers having the relative stereochemistry of substituents on either of the THF rings varied have been also synthesized. All four diastereomers have been subjected for extensive NMR studies and their C-13 NMR chemical shifts have been compared with notoryne and laurendecumenyne B. In addition, chemical shifts for the four diastereomers along with these natural products were calculated with the help of DFT calculations and compared to the experimentally obtained chemical shift values.

Unified approach for the total aynthesis of Bis-THF C-15 acetogenins: a chloroenyne from laurencia majuscula, laurendecumenyne B and laurefurenynes A/B - Senapati, Sibadatta; Unmesh, Nivedya A.; Shet, Manoj N.; Ahmad, Iram; Ajikumar, Nandu; Ramana, Chepuri V. (Synthesis-Stuttgart, 2021)
A highly diastereoselective total synthesis of several bis-THF C-15 acetogenin natural products, chloroenyne from Laurencia majuscula, laurendecumenyne B, and laurefurenyries A/B, is reported. Additionally the synthesis of an advanced intermediate reported in the earlier total synthesis of (E/Z)-elatenynes (formal synthesis) is described. The salient features in the synthesis include epoxide opening, Birch reduction, Sharpless asymmetric dihydroxylation-cycloetherification, S(N)2 halogenation, and a relay cross metathesis.
Keywords: bis-THF C-15 acetogenins; carbohydrate building block; relay-cross-metathesis; S(N)2 halogenation; Sharpless asymmetric dihydroxylation-cycloetherification

Unified approach for the total synthesis of Bis-THF C-15 acetogenins: a chloroenyne from laurencia majuscula, laurendecumenyne B and laurefurenynes A/B - Senapati, Sibadatta; Unmesh, Nivedya A.; Shet, Manoj N.; Ahmad, Iram; Ajikumar, Nandu; Ramana, Chepuri V. (Synthesis-Stuttgart, 2021)
A highly diastereoselective total synthesis of several bis-THF C-15 acetogenin natural products, chloroenyne from Laurencia majuscula, laurendecumenyne B, and laurefurenyries A/B, is reported. Additionally the synthesis of an advanced intermediate reported in the earlier total synthesis of (E/Z)-elatenynes (formal synthesis) is described. The salient features in the synthesis include epoxide opening, Birch reduction, Sharpless asymmetric dihydroxylation-cycloetherification, S(N)2 halogenation, and a relay cross metathesis.
Keywords: bis-THF C-15 acetogenins; carbohydrate building block; relay-cross-metathesis; S(N)2 halogenation; Sharpless asymmetric dihydroxylation-cycloetherification